THE DEVELOPMENT OF PARTICIPATIVE MANAGEMENT MODEL OF PRIMARY CARE UNITS, STAR-RATED SUB-DISTRICT HEALTH PROMOTING HOSPITAL IN UDONTHANI PROVINCE - ศิรินิกร เรวัฒน์; คำหารพล ฐนกร (Primary Health Care Journal (Northeastern Edition), 2023)
This participatory action research the objective is to the development of participative management model of primary care units, star-rated sub-district health promoting hospital in Udon Thani province. The study was conducted between July and September 2023. The sample group was the star-rated sub-district health promoting hospital development committee, totaling 379 people. The study is divided into 3 phases: Phase 1 studies the conditions, problems, and approaches to participatory management; Phase 2 develops the participatory management model; and Phase 3 evaluates the participatory management model. Tools used to collect data include questionnaires, organizing workshops, and meetings to listen to opinions. The data were analyzed using percentage, mean, and standard deviation statistics. and synthesize content information. The research results found that participation in receiving benefits from plans and projects was at the highest level, with a mean of 4.53 (SD = 0.50), and in planning and decision-making. Operational aspects were at a high level, mean 4.43 (SD = 0.84), mean 4.12 (SD = 0.89), respectively, and it was found that the plan/project evaluation aspect was at a low level, mean 2.87 (SD = 0.72). The development of a participatory management model has 6 elements: 1) model principles; 2) model objectives; 3) input factors; 4) participatory management process; 5) model outputs; and 6) success condition factors. After using the participatory management model was found that the averages were at a high level for every component, appropriateness averaged 4.20 (SD = 0.62), feasibility averaged 4.10 (SD = 0.55), and usefulness averaged 4.24 (SD = 0.62).